A server-client version of “Genomatica” integrated genome information browser - Mori, Hirotada; Ogasawara, Naotake; Yakoh, Takahiro; Akiyama, Yutaka (Genome Informatics, 1994)
We have been developing a new server-client version of “Genomatica”, an integrated data management and analysis tool for supporting genome sequencing projects. Now the client browser can work even with no local data file, retrieving the latest genome information maintained at the Genomatica server sites. The server-client communication is based on HTTP (HyperText Transfer Protocol). The previous version of Genomatica system [1] was designed for the use by expert information managers of a genome sequencing project. The old system always required a large amount of disk space on local machine for storing several files of whole genome data. New server-client version is upper-compatible to the previous system and it allows general users to access genome information files maintained at remote server sites. Location of each local or remote file can be customized at the system configuration menu using URL (Unified Resource Locator) representation. In order to improve response time, users may keep local copy of some basic data files, downloading from the Genomatica servers. Also users can overlay their private genome sequences and/or comments onto the public genome information supplied from the server. The system is running on Unix workstations with X11-Motif window environment. The client program and several E.coli and B.subtilis data files are available on the GenomeNet ftp server (ftp.genome.ad.jp).